Fiscal Deficits and Economic Growth in Nigeria: A Chow Test Approach - Edame, Greg Ekpung; Okoi, Okoiarikpo Benjamin (International Journal of Economics and Financial Issues, 2015)
The recent criticism of poor fiscal performance levelled against the democratic regimes in Nigeria has resulted in questions being asked as to the soundness of the acclaim which heralded its advent. Such questions generally focus on the growth impacts of the deficits incurring during this regimes. In view of this, this study examined the relative impact of fiscal deficits on economic growth in Nigeria during the military and democratic regimes. The study employed Chow endogenous break test, unit root and cointegration tests. The results derived from the Chow test analysis reveal that there is a difference between the growth-impact of fiscal deficit in the two regimes. In particular, the study found that fiscal deficits had a significant growth-impact during the military regime, while it has not had a significant impact on economic growth during the democratic regime. On the other hand, the study’s` results indicated that the interest rate did not have a significant growth-impact during both regimes, while the gross fixed capital formation had a significant growth impact during both regimes In view of the findings, the study recommended the strengthening of the country`s budgetary institutions so as to ensure the de-politicization of the budgetary process. Furthermore, the study recommended the reduction in the current lending rate so as to ensure increased access to investment funds by domestic entrepreneurs. Keywords: Fiscal deficit; Economic growth; Chow test; Military regime; Democratic regime. JEL Classifications: C40; D53; E42; G17; O23; O40; P43.